Visible marking of wader nests to avoid damage by farmers does not increase nest predation. Issue 2 (20th February 2017) - ZÁMEČNÍK, VÁCLAV; KUBELKA, VOJTĚCH; ŠÁLEK, MIROSLAV
Summary: Only a few studies have assessed the predation risk on artificially marked nests, or have examined ways of marking nests to avoid destruction by machinery. Until now, however, neither type of study has directly addressed this apparent trade-off experimentally. The impact of marking the nests of Northern Lapwing Vanellus vanellus with thin 2 m-long conspicuous bamboo poles with the top end highlighted with reflective red or orange spray has been tested for three years in two breeding areas of waders in the Czech Republic. A total of 52 pairs of nests on agricultural land, with each pair consisting of one marked nest and one unmarked reference counterpart nest, were monitored for 2004 nest-days until hatching, agricultural operations or failure. The results proved that marking itself does not result in increased nest predation. The nests found in the early incubation stage were under higher threat of depredation, irrespective of the presence of marking. Our results show that it is possible to find a finely-tuned trade-off in nest marking of ground-nesting birds between risk of damage by agricultural machinery and risk of increased nest predation. Our positive experience with Northern Lapwing, and episodically with three other wader species in the Czech Republic, suggests that this direct nest protection could be used effectively for a wider variety of ground-nesting birds.